Pathological Changes in the Respiratory Tract of Goats Infected by Pasteurella multocida B:2 - Shamsuddin, Mohd Shafarin; Saad, Mohd Zamri; Bejo, Siti Khairani; Saharee, Abdul Aziz (2008 Elsevier Ltd., 2009)
Clinical and pathological changes are described in groups of five goats pretreated with dexamethasone and then infected with a large dose of Pasteurella multocida B:2 (the cause of haemorrhagic septicaemia) by the intratracheal, subcutaneous or intranasal route (groups A, B and C, respectively). In group A, two goats died (on day 1 and 4 post-inoculation); in group B three died (days 2, 5 and 14); and in group C one died (day 20). The infecting organism was recovered from the four goats that died within#5 days. The major pulmonary lesions included acute pneumonia, congestion, oedema and hydrothorax. Subcutaneous oedema of the lower jaw and brisket, typically seen in cattle and buffalo, was absent in goats.